PENGARUH MODEL BLENDED PROBLEM BASED LEARNING BERBASIS LMS MOODLE TERHADAP MOTIVASI BELAJAR DAN HASIL BELAJAR MAHASISWA JURUSAN AKUNTANSI - M. Miftach Fakhri; Anwar Wahid; Della Fadhilatunisa; Dewi Fatmarani Surianto; Muhammad Fajar B; Akmal Hidayat (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2022)
This study aims to find out the Moodle LMS-based blended problem-based learning model which has an effect in improving student learning outcomes and motivation and differences in student learning outcomes and motivation provided by blended problem-based learning model learning based on Moodle LMS with students following a blended learning model. The research design carried out is quasi-experimental (quasi-experimental). The research sample consisted of class A as many as 34 people as an experimental class and class D as many as 33 people as a control class. The sampling technique is purposive sampling. The results of the study explained that the inferential h asil análisis with the paired simple t test explained that the t-count value is greater than the t-table with a sig value smaller than 0.05 which means that the implementation of a blended problem-based learning model can help increase student learning outcomes and motivation. In addition, the results of the independent simple t test explained that the t-count value is greater than the t-table with a sig value smaller than 0.05 which is meaningful, namely the results and learning motivation of experimental class students have significant differences with control class students.